2003
DOI: 10.1002/cncr.11476
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HER‐2 overexpression in ovarian carcinoma tissue and its prognostic value in patients with ovarian carcinoma

Abstract: BACKGROUNDThe HER‐2 (Human Epidermal Growth factor receptor‐2, also known as c‐erb‐2/neu) protooncogene encodes a transmembrane receptor protein, Mr 185,000. Studies have shown that the HER‐2 oncogene is overexpressed in approximately 25–30% of ovarian carcinoma (OC) cases, but to the authors' knowledge, to date no consensus regarding overexpression and prognosis has been possible. The objective of the current study was first to analyze the presence of HER‐2 overexpression in tissue from Danish OC patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 30 publications
8
83
0
Order By: Relevance
“…In other studies, the percentage of c-erb-B2-positive tumors ranged from 15% to 30%. 12,21,22 It is noteworthy that c-erb-B2 overexpression in our series was observed only in carcinomas: mostly in highgrade carcinomas. Surprisingly, despite this correlation with aggressive morphology, results of the survival study did not indicate statistical significance.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In other studies, the percentage of c-erb-B2-positive tumors ranged from 15% to 30%. 12,21,22 It is noteworthy that c-erb-B2 overexpression in our series was observed only in carcinomas: mostly in highgrade carcinomas. Surprisingly, despite this correlation with aggressive morphology, results of the survival study did not indicate statistical significance.…”
Section: Discussionmentioning
confidence: 55%
“…Surprisingly, despite this correlation with aggressive morphology, results of the survival study did not indicate statistical significance. Although the predictive value of c-erb-B2 in ovarian carcinomas is not clear, some studies have shown a significantly worse prognosis for patients with positive tumors, 11,12,21 whereas others did not observe this correlation. [23][24][25] Similarly, EGFR reportedly was overexpressed in 30% to 77% of ovarian carcinomas, and its association with a poor prognosis, like in our series, was not verified.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the ErbB-2 antibody treatment Herceptin is clinically effective in treating a subset of breast cancer patients (21). Overexpression of ErbB-2 also correlates with poor outcome in ovarian cancer (41,42), although antibody therapy for ErbB-2 is not used clinically for the treatment of ovarian cancer. ErbB-2 is expressed in OSE cells (43) in approximately 25% to 30% of ovarian cancer (41,44,45) and in cultured ovarian cancer cells, including SKOV3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For OC, 20-30% of primary stage III/IV tumours show ERBB2 overexpression (Hellstrom et al, 2001). Protein expression using antibody staining on a subset of ovarian tumours from the MALOVA study showed that 39% of the carcinomas overexpressed ERBB2 (Hogdall et al, 2003b).…”
mentioning
confidence: 99%